PERKEMBANGAN HUKUM PERDATA DI INDONESIA TINJAUAN HISTORIS DAN KONTEKSTUAL - Arif, Zuhri (ISLAMIC BUSSINESS LAW REVIEW, 2024)
Abstract: Changes and developments in civil law occur because law is dynamic, and is also influenced by Human civilization is increasingly shifting day by day along with technological developments and global warming. Civil law is essentially closely related to internal strengthening control function that replaces the external supervision function. Modern civil development law because its basis is always related to the relationship between the government regime and community, thereby strengthening the participatory role of society in one aspect. One Forms of civil law modernization that are developing include, among others; Contract law, consumer protection law, and employment law, as a form of strengthening internal functions related to external control function.Keywords: Civil law, Developments, Change